(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
Today, among ophthalmological diseases, eyelid epithelial tumors account for approximately 85–90% of all eyelid tumors. Although benign tumors are also common among them, malignant tumors (especially basal cell carcinoma) are one of the most common diseases encountered in clinical practice. In general, solar radiation, environmental factors, decreased immunity in the human body, and age factors play an important role in the development of these tumors. Therefore, in-depth study of the morphological and immunohistochemical characteristics of epithelial tumors is an important role in the development of early diagnosis and effective treatment tactics.